Theory of Optimal Currency Zones: from Classics until Today - Pinchuk Anastasiya K. (Bìznes Inform, 2013)
The article analyses evolution of the theory of optimal currency zones (OCZ), starting from its classical provisions until moder developments. Based on the critical analysis of classical criteria of OCZ, the article develops a scheme of selection of the currency mode by the Robert Mundell theory. It considers achievements of the alternative OCZ theory, the main provisions of which are shown schematically in the form of illustrations of evolution of the theory of optimal currency zones. In the result of analysis of classical criteria of optimal currency zones and generalisation of developments of the new OCZ theory, the article develops a universal algorithm of identification of optimal conditions for an efficient currency zone. Using this algorithm allows identification of a system of quantitative indicators of expediency of regional joining the OCZ, on the basis of which one can build an economic model of an optimal currency zone, which reflects the degree of readiness of any country to join or develop the OCZ. Development of this model is necessary for many countries that face the need to select the currency integration. This model is of special importance for Ukraine, for which it is important to select the course of external integration, since various directions of foreign policy significantly influence efficiency of the domestic economic policy in the country.